Job satisfaction among frontline police officers in China: the role of demographic, work-related, organizational and social factors - Chen, Zheng (Psychology, crime & law, 2018)
This study was intended to add to information about the underinvestigated policing studies in China. The possible impact of demographic characteristics, work-related variables, and organizational management and social variables on police job satisfaction was investigated. Data were collected through a self-report survey administered to a sample of sworn police officers training in a national police university in China (N = 393). Results indicated that work-related characteristics associated with variety and stress, and organizational variables associated with professional development and peer cohesion were the most important predictors of job satisfaction in this sample of police officers.